2010
DOI: 10.1111/j.1346-8138.2010.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐tuberculous mycobacterial infections of the skin: A retrospective study of 29 cases

Abstract: The incidence of infections caused by non-tuberculous mycobacteria has increased in recent years, due to a rise in dermatological procedures and a greater prevalence of immunosuppression in the general population. This study investigated the clinical and microbiological findings of non-tuberculous mycobacterial skin infections. The study population included 29 patients from whom non-tuberculous mycobacteria were cultured after isolation from skin biopsy materials, cutaneous abscesses or exudates. Clinical, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 15 publications
7
80
2
1
Order By: Relevance
“…A good therapeutic response was obtained. were the most common [7]. One curious finding, which was observed by Camargo et al, in 82% of their cases, was well-defined, clear, round vacuolar spaces, some of which contained conglomerates of acid-fast bacilli.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A good therapeutic response was obtained. were the most common [7]. One curious finding, which was observed by Camargo et al, in 82% of their cases, was well-defined, clear, round vacuolar spaces, some of which contained conglomerates of acid-fast bacilli.…”
Section: Discussionmentioning
confidence: 90%
“…The most common histopathological presentation was abscesses surrounded by epithelioid and Langhans' giant cells (80% of the cases), while 15% of the cases involved abscesses with a discrete granulomatous component, and in 5% the granulomatous component was absent [5]. Also, Lee et al, found marked granulomatous inflammation in 86% of their biopsied cases [7]. Suppurative and mixed granulomas…”
Section: Resultsmentioning
confidence: 99%
“…13 The severity of the disease depends on immune status, extension of cutaneous injury, and direct inoculation. 14 Disseminated infections have been reported and usually occur in immunocompromised patients. Especially patients receiving corticosteroid mono -or combination -therapy, as well as patients treated with anti-TNF in combination with other immune modulating substances run the risk of severe and critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of solitary lesions occur on the lower extremities, but the upper extremities, trunk, and rarely head and neck may also be involved. 9,10 Additionally, there are a number of reports of cutaneous M chelonae infections in immunocompetent hosts due to subcutaneous inoculation with contaminated tattoo ink, 8,11,12 after acupuncture, 13,14 and after mesotherapy. 15 Mycobacterium abscessus, M chelonae, Mycobacterium conceptionense, and M fortuitum have all been isolated in postoperative infections after plastic surgery procedures.…”
Section: Clinical Featuresmentioning
confidence: 99%